PANDANGAN EKONOMI ISLAM TERHADAP FINTECH PEER TO PEER LENDING PADA GENERASI Z - Intan Ayu (Dar el-Ilmi : jurnal studi keagamaan, pendidikan dan humaniora, 2023)
This study aims to analyze how the practice of developing Peer to Peer Lending-based technology systems in generation Z according to the view of Islamic economics, especially as payment transactions. In this study the authors designed a research design with a qualitative approach using the interview method with Z generation informants in Karangtaruna Kediren Village who had been married for research data collection. The results of this study indicate that there is a generation Z view in Karangtaruna Kediren Village towards the development of a financial technology system based on fintech lending. Members of Karangtaruna Desa Kediren continue to take advantage of the development of the fintech lending-based financial technology system for the convenience of borrowing money even though it applies usury. Whereas the practice of online loans that apply a total payment of more than the initial principal amount of the loan is not justified from an Islamic economic perspective. Keywords: Fintech lending, Islamic economics